2020
DOI: 10.17309/tmfv.2020.4.05
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Related Peculiarities of 7-Year-Old Schoolchildren’s Motor Fitness

Abstract: The purpose of the study was to identify gender-related peculiarities of 7-year-old schoolchildren’s motor fitness.  Materials and methods. The study participants were 59 7-year-old schoolchildren (girls – 27, boys – 32). The children and their parents were informed about all the features of the study and gave their consent to participate in the experiment. The study used the following research methods: analysis of scientific and methodological literature, pedagogical observations, testing of motor fitness, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In DA the acceptable classification accuracy rate was set at ≥95% with the classification error rate ≤5%. (Iermakov, Ivashchenko, Khudolii, Chernenko, Veremeenko, & Zelenskyi, 2021;Ivashchenko, Nosko, Bartik, & Makanin, 2020 (Sec.). We used only Log 10 -transformed data for DA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In DA the acceptable classification accuracy rate was set at ≥95% with the classification error rate ≤5%. (Iermakov, Ivashchenko, Khudolii, Chernenko, Veremeenko, & Zelenskyi, 2021;Ivashchenko, Nosko, Bartik, & Makanin, 2020 (Sec.). We used only Log 10 -transformed data for DA.…”
Section: Discussionmentioning
confidence: 99%
“…DA and PCA are both used to reduce the dimensionality and noise level of sEMG data. DA provides better classification accuracy between groups by maximizing the ratio of between and within-group variance (Ivashchenko, Nosko, Bartik, & Makanin, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal studies have shown that children with low motor competence tend to be less physically active than children with higher motor competence, and that trend continues through adolescence and adulthood (Barnett et al, 2008;Hands, 2008). Furthermore, motor competence has been related to physical fitness (Ivashchenko, Nosko, Bartik, & Makanin, 2020;Haga, 2008a;Hands, 2008) and self-perception (Barnett, Morgan, van Beurden, & Beard, 2008;Vedul-Kjelsås, Sigmundsson, Stensdotter, & Haga, 2012). On the contrary, reduced physical activity in children with low motor competence may be associated with lower performance levels on several components of physical fitness, such as cardiovascular endurance, muscular strength and endurance, and speed (Haga, 2008b;Hands, 2008;Tsiotra, Nevill, Lane, & Koutedakis, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…As in the studies by Ivashchenko, Nosko, Bartik, & Makanin (2020), Iermakov, Ivashchenko, & Khomiakov (2020), non-significant differences in the level of development of motor coordination and statistically significant differences in the level of development of strength, speed strength, speed, endurance, and in the level of proficiency in gymnastic exercises between girls and boys were observed, which indicates a need for dedicated development of motor skills. Such development is possible in teaching physical exercises with the use of programmed materials, as indicated by literature data (Shueva, Ivashchenko, & Jagiello, 2021;Suprun, Ivashchenko, & Cieślicka, 2021;Kharkovshchenko, 2022).…”
Section: Discussionmentioning
confidence: 52%